Rural Library System - Sugra Begum, R.; Ranganathan, T. (Journal of Information and Knowledge, 1964)
On the basis of the Census of 1961, calculates the number of Rural Central Libraries as 315, of Rural Branch Libraries as 6,580, of Librachines as 12,607 and of the Rural Service Stations as 241,366.